Faktor Usia Ibu dan Paritas Meningkatkan Kejadian Mioma Uteri - Army Novitasari; Gangsar Indah Lestari; Martini Fairus (Jurnal Kesehatan Metro Sai Wawai, 2018)
Background: The most common reproductive disease among Indonesian women is uterine myoma. The number of occurrences of this disease in Indonesia ranks second after cervical cancer. Purpose: This study aims to determine the relationship between maternal age and parity with the incidence of uterine myoma at Mardi Waluyo Metro Hospital in 2016. Methods: This study uses a cross sectional design. The study sample was 141 respondents. The independent variable of the study was maternal age and parity, while the dependent variable was uterine myoma. Data analysis using univariate and bivariate analysis. Bivariate analysis using chi square test. Results: The results showed that there was a relationship between maternal age (p = 0,000) and parity (p = 0,000) with the incidence of uterine myoma at Mardi Waluyo Metro Hospital. Conclusion: The conclusions of this study are maternal age and parity are factors that increase the incidence of uterine myoma. Prevention efforts and reducing the incidence of uterine myoma need to be improved by early detection of women with age and risky parity.